2019
DOI: 10.1167/iovs.18-25700
|View full text |Cite
|
Sign up to set email alerts
|

Early Optic Nerve Head Glial Proliferation and Jak-Stat Pathway Activation in Chronic Experimental Glaucoma

Abstract: Purpose We previously reported increased expression of cell proliferation and Jak-Stat pathway–related genes in chronic experimental glaucoma model optic nerve heads (ONH) with early, mild injury. Here, we confirm these observations by localizing, identifying, and quantifying ONH cellular proliferation and Jak-Stat pathway activation in this model. Methods Chronic intraocular pressure (IOP) elevation was achieved via outflow pathway sclerosis. After 5 weeks, ONH longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 104 publications
3
55
0
Order By: Relevance
“…In this study, we confirmed the proliferation of both microglia and astrocytes in the UON of mouse after 3 days of IOP elevation. While some investigators have stated that most proliferating cells in the glaucoma ON are Iba1 positive microglia, 25 our findings agree with those of Lozano and co-workers that, while microglia and astrocytes both proliferate 56 , astrocytes remain the majority of glia in the glaucomatous ON. In chronic experimental glaucoma in monkey, the total number of glia appeared constant, though the proportionate area of glia increased with axonal loss.…”
Section: Astrocyte Ultrastructuresupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we confirmed the proliferation of both microglia and astrocytes in the UON of mouse after 3 days of IOP elevation. While some investigators have stated that most proliferating cells in the glaucoma ON are Iba1 positive microglia, 25 our findings agree with those of Lozano and co-workers that, while microglia and astrocytes both proliferate 56 , astrocytes remain the majority of glia in the glaucomatous ON. In chronic experimental glaucoma in monkey, the total number of glia appeared constant, though the proportionate area of glia increased with axonal loss.…”
Section: Astrocyte Ultrastructuresupporting
confidence: 92%
“…51 Astrocytes are the most numerous glia cell in mammalian ONH 52 and the reaction of astrocytes to injurious stimuli is now recognized to be either beneficial or detrimental. 53,54,55 Designated as A2 astrocytes, the beneficial phenotype activates the JAK-STAT pathway 56 and STAT knockout in mouse glaucoma leads to greater ganglion cell loss 25 . The detrimental A1 astrocytes arise from stimulation from microglia with interleukin 1α, tumor necrosis factor α (TNFα) , and complement component subunit 1q (C1q) .…”
Section: Astrocyte Ultrastructurementioning
confidence: 99%
“… 62 However, significant astrocyte proliferation has been reported by Ki67 labeling in mice 1 week after IOP elevation 46 and in rat glaucoma models. 63 Thus, some of the increase in nuclear clusters may be caused by a proliferation of astrocytes or microglia. Because external stresses are transmitted from the plasma membrane via the cytoskeleton to the nucleus, a change in nuclear shape or conformation is expected, as we observed and has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of rat ONH showed that the ON consists of 78% astrocytes. 63 The GFAP antibodies had limited depth penetration in sections, necessitating our image capture from the more superficial layer of each section. The axonal compartments were inferred from the negative space of binarized actin and nuclear images, which could include extracellular fluids or voids.…”
Section: Discussionmentioning
confidence: 99%
“…A general retraction of astrocytes from PPS followed by complete astrocyte loss was reported in one rat glaucoma model [ 66 ]. This finding was contradicted by abundant astrocyte division found in another rat glaucoma model [ 67 ]. In mouse glaucoma and in a monkey glaucoma model [ 68 ], there was minimal astrocyte death, as indicated by only occasional apoptotic ultrastructure and TUNEL labeling.…”
Section: Discussionmentioning
confidence: 93%